Climate change predictions on track: Victoria University expert - Editors (New Zealand Science Review, 2012)
​A new report co-authored by David Frame, Director of the New Zealand Climate Change Research Institute at Victoria University, has confirmed that climate change predictions made 20 years ago are proving reasonably accurate.